Tourism planning in small tropical islands: methodological considerations and development issues in Samoa - Douglas G. Pearce (Études Caribéennes)
This chapter seeks to contribute to a greater understanding of tourism on small tropical islands and to tourism planning in this context by outlining aspects of the methodology used in the preparation of the Samoa Tourism Development Plan 2002-2006 and by discussing some of the issues that arose from this process. In particular, the chapter presents a ‘question-asking’ approach that involves wide-ranging stakeholder consultation to identify and then address key issues, namely: - How much tourism does Samoa want and at what rate should it be developed over the next five years? - What will the growth of tourism in Samoa over the period 2002-2006 depend on? - What forms of tourism should be developed and where? - What are the most appropriate processes of tourism development for Samoa? The strategies formulated in the plan are then outlined. The paper concludes that local participation, while invaluable, is by itself insufficient for the preparation of an effective tourism development plan.